Physiological and molecular aspects of seed longevity: exploring intra‐species variation in eight Pisum sativum L. accessions. Issue 3 (18th May 2022) - Gianella, Maraeva; Doria, Enrico; Dondi, Daniele; Milanese, Chiara; Gallotti, Lucia; Börner, Andreas; Zannino, Lorena; Macovei, Anca; Pagano, Andrea; Guzzon, Filippo; Biggiogera, Marco; Balestrazzi, Alma
Abstract: Conservation of plant genetic diversity is fundamental for crop improvement, increasing agricultural production and sustainability, especially in the face of climatic changes. Although seed longevity is essential for the management of seed banks, few studies have, so far, addressed differences in this trait among the accessions of a single species. Eight Pisum sativum L. (pea) accessions were investigated to study the impact of long‐term (approximately 20 years) storage, aiming to reveal contrasting seed longevity and clarify the causes for these differences. The outstanding seed longevity observed in the G4 accession provided a unique experimental system. To characterize the biochemical and physical status of stored seeds, reactive oxygen species, lipid peroxidation, tocopherols, free proline and reducing sugars were measured. Thermoanalytical measurements (thermogravimetry and differential scanning calorimetry) and transmission electron microscopy combined with immunohistochemical analysis were performed. The long‐lived G4 seeds neither consumed tocopherols during storage nor showed free proline accumulation, as a deterioration hallmark, whereas reducing sugars were not affected. Thermal decomposition suggested a biomass composition compatible with the presence of low molecular weight molecules. Expansion of heterochromatic areas and reduced occurrence of γH2AX foci were highlighted in the nucleus of G4 seeds. The longevity of G4 seeds correlates with the occurrence of a reducing cellular environment and a nuclear ultrastructure favourable to genome stability. This work brings novelty to the study of within‐species variations in seed longevity, underlining the relevance of multidisciplinary approaches in seed longevity research.